Penerapan Metode Forward Chaining Pada Sistem Pakar Untuk Mengetahui Kepribadian Seseorang - Ranti Eka Putri; Kriscillia Molly Morita; Yanti Yusman (INTECOMS: Journal of Information Technology and Computer Science, 2020)
Personality is the overall behavior and emotions that become a unique characteristic of someone who is stable and predictable. Characteristics or personality traits affect directly or indirectly on work and family conflicts. To find out someone's personality type, generally a person must consult directly with a psychologist or by conducting a questioner that is provided to find out which personality types he belongs to. By utilizing technology that is rapidly developing nowadays, a system that can help people to know their personality is needed or needed, the system is an expert system. This expert system was built using the forward chaining method. This expert system is designed and built with the PHP programming language or often called a web-based system. Due to the web-based system, system users will not be limited by space, time, and minimize the cost and energy to find out which personality belongs to which type of personality